Sensitivity of fiscal-policy effects to policy coordination and business cycle conditions - Matti Virén (Bank of Finland, 2013)
This paper deals with the problems of assessing the effects of fiscal policy in the European Monetary Union. Here, we face wide cross-country differences in key fiscal parameters, some of which may also be vary over time (business cycle). Moreover, these effects may also depend on trade spillover effects and thus on the extent of policy coordination. Our empirical analyses make use of data for 15 EU countries, mainly for the period 1970-2011. The results clearly indicate that fiscal multipliers are not constant across countries and time, being much larger during economic recessions. By contrast, the policy coordination-effects appear to be more homogenous, although it turns out that small countries may benefit more from coordination.
URN:NBN:fi:bof-20140807584
Keywords: H62; E61; E63; 330; Fiscal policy; policy coordination; government deficit; EMU Classification